Ensemble Learning based Fishing Behavior Analysis for Vessels around Zhoushan Islands Erea. Issue 1 (1st March 2022) - Zhang, Liang; Xing, Bowen; Chen, Xiao; Wang, Wugui
Abstract: In order to improve and verify the application value of AIS data in fishing behavior analysis, three existing models were chosen to analyze the fishing paths of more than 200 boats around Zhoushan Islands. In order to confirm their operation mode, F1-score was used to evaluate related models. Experimental results shown that the Lightgbm model embodies better performance in the analysis of fishing boat behavior with higher practicality.